Digital media use among older adults during the COVID-19 pandemic: a scoping review - Juliana Cordeiro Carvalho; Gabriela Cabett Cipolli; Vanessa Alonso; Meire Cachioni (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: To identify and map the purpose of digital media use among older adults during the coronavirus disease (COVID-19) pandemic. Methods: A scoping review was conducted using the Joanna Briggs Institute methodology involving a search of 7 databases for relevant articles in English, Spanish, and Portuguese published between 2020 and 2021. Most studies were retrieved from the SCOPUS and Web of Science databases. The inclusion criteria for this review were: participants - individuals aged ≥ 60 years; concept - digital media use during the pandemic; context - community-dwelling older adults. Results: The search led to the retrieval of 1992 studies. The titles and abstracts were screened by 2 independent reviewers. Full texts were then extracted according to the inclusion criteria, reaching a total of 12 articles for the review. The results showed that the main purposes of digital media use by older adults were to access and answer surveys sent by e-mail or posted on social media and virtual social networks (eg, Facebook, Instagram, and/or Twitter) and also for telemedicine consultations. Conclusions: Adherence and acceptance of technologies and digital media are considered important factors for their use by older adults. However, a large contingent of the older population does not have access to, or require assistance for, information and communication technologies, mainly in low- and middle-income countries, making the promotion of digital literacy fundamental in this population